Sequential novel use of Moringa oleifera Lam., biochar, and sand to remove turbidity, E. coli, and heavy metals from drinking water - Ahsan Shah; Arun Arjunan; Georgina Manning; Maryam Batool; Julia Zakharova; Alisha J. Hawkins; Fatima Ajani; Ioanna Androulaki; Anusha Thumma (Cleaner Water)
This research investigates the individual and combined use of Moringa oleifera (MO) Lam., biochar, and sand to remove turbidity, pathogens, and heavy metals from drinking water. Contaminated water was synthetically prepared using kaolin, standard nickel/lead solutions, and Escherichia coli (E. coli). The optimal dose of MO seed protein, extracted in 1 M NaCl solution, was determined using a jar test flocculator. MO treatment reduced water turbidity from 200 to 4 NTU and achieved a 1–2 log reduction in E. coli from an initial count of 1×105 CFU/ml. Nevertheless, no significant reduction in nickel and lead concentrations was noted. Subsequently, the MO-treated water was passed through a biochar column supported on a sand bed, revealing clear water with 1 NTU turbidity and no trace of E. coli counts being detected. The sequential process of using biochar and sand reduced nickel and lead by 97.5 % and 99.3 %, respectively. The physicochemical properties of the treated water met WHO and UK standards for safe drinking water. All experiments were performed in duplicates (n=2; P < 0.05). The scalability and economic feasibility of the project, the mechanism of removal of contaminants by MO and biochar, and the study's limitations are also discussed.